Awareness and practice regarding cervical cancer screening among women visiting a tertiary hospital of Kathmandu - Parajuli, Puspa; Paudel, Narayani; Dahal, Sunita (Journal of Kathmandu Medical College, 2019)
Background: Cervical cancer is the leading female cancer in Nepal. Fortunately, it is preventable by detectingprecancerous lesions and by various screening tools for early invasive cancers. Screening can be possible if women are aware of the problem. Despite the existence of effective screening using Pap smear, the uptake of screening is poor.Objectives: The objective of this study was to assess the awareness and practice regarding cervical cancer screening among women visiting tertiary hospital.Methodology: A descriptive cross – sectional study was conducted to assess the awareness and practice regarding cervical cancer screening among women attending in gynaecological outpatient department of Kathmandu Medical College Teaching Hospital. A total of one hundred and fifty two women were selected purposively for the study. Structured questionnaire was designed and data collection was done through face to face interview technique during the period of September to November 2018. The collected data were analyzed by using Statistical Package for Social Science version 20.Results: Among 152 respondents, majority of the respondents (59.2%) were aware that multiple sexual partners is one of the risk factors of cervical cancer. 38.8% were aware that cervical cancer can be prevented by regular cervical screening. Majority of the respondents: 152 (44.7%) had given correct response regarding meaning of cervical cancer screening and 42.8% were aware of Pap smear test for cervical screening. Only 31.6% had performed cervical cancer screening at least once. Overall mean percentage knowledge was 3.08 with SD 0.96.There was weak correlation between knowledge and practice.Conclusion: This study concluded that majority of respondents had inadequate knowledge and practice regarding cervical cancer screening. Thus, cervical cancer screening health camps and awareness program should be conducted at community to national level for women, to increase the level of knowledge and practice regarding cervical cancer screening.